VD_FINDINFO AP / 2011 / 120 vom 18. August 2011 - VD Tribunal cantonal (2011)
HEURES DE TRAVAIL SUPPLÉMENTAIRES, CONTRAT DE TRAVAIL, DROIT AU SALAIRE | 321c al. 3 CO, 13 LTr, 308 al. 1 let. a CPC (CH)